TOW TRUCKS - Dieker, Wendy Strobel (Mankato, Minnesota : Amicus/Amicus Ink, 2019)
This book invites early readers to look for new vocabulary words and pictures while giving simple facts about tow trucks and how they haul wrecked vehicles from accident scenes or other scenarios.
Keywords: Wreckers (Vehicles) -- Children's nonfiction